Tailoring a sexual health curriculum to the sexual health challenges seen by midwifery, nursing and medical providers and students in Tanzania - B.R. Simon Rosser; Dickson A. Mkoka; Corissa T. Rohloff; Lucy R. Mgopa; Michael W. Ross; Gift G. Lukumay; Inari Mohammed; Agnes F. Massae; Ever Mkonyi; Stella E. Mushy; Dorkasi L. Mwakawanga; Nidhi Kohli; et al. (AOSIS, 2022)
Background: Tanzania is a country experiencing multiple sexual health challenges, but providers receive no formal training in sexual health. Aim: This study aimed to assess (1) what sexual health challenges are commonly seen in clinics in Tanzania, (2) which are raised by patients, (3) which are not addressed and (4) which topics to prioritise for a sexual health curriculum. Setting: Healthcare settings in Tanzania. Methods: Participants were 60 experienced and 61 student doctors, nurses and midwives working in Dar es Salaam. The authors conducted 18 focus groups stratified by profession (midwifery, nursing or medicine) and experience (practitioners vs. students). Results: Providers identified six common sexual health concerns: (1) Human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) and sexually transmissible infection (STI) (especially syphilis and gonorrhoea), (2) sexual violence (including intimate partner violence and female genital mutilation), (3) early and unwanted pregnancy (including early sexual debut and complications from abortion), (4) sexual dysfunctions, (5) key population concerns (e.g. lesbian, gay, bisexual, transgender (LGBT); sex work) and (6) non-procreative sexual behaviour (including pornography and masturbation in males and oral and anal sex practices in heterosexual couples). Across professions, few differences were observed. Homosexuality, sex work, masturbation and pornography were identified as taboo topics rarely discussed. Most participants (81%) wanted one comprehensive sexual health curriculum delivered across disciplines. Conclusion: A sexual health curriculum for health students in Tanzania needs to address the most common sexual health concerns of patients. In addition to teaching sexual science and clinical care, skills training in how to address taboo topics is recommended. Students endorsed almost all sexual health topics, which suggests that a comprehensive curriculum is appropriate.